DETERMINAN PILIHAN KARIR PADA MAHASISWA AKUNTANSI (Studi Empiris pada Mahasiswa S1 Akuntansi Manajerial Politeknik Negeri Samarinda) - Zulfikar Zulfikar; Nyoria Anggraeni Mersa (Jurnal Eksis, 2015)
ZULFIKAR dan NYORIA ANGGRAENI MERSA.This study aims to determine whether the financial reward factors, work environment, labormarket considerations, personality, and gender influence for the students of the managerial accounting, State Polytechnic of Samarinda in choosing a profession as an accountant. This study use data survey method that uses primary data obtained from questionnaires. The population in this study was a mid-level accounting students of the managerial accounting, State Polytechnic of Samarinda. The number of samples taken in this researchare 87 students.Tool data used inthisstudy using differenttestt-test and discriminant analysis using SPSS20. Analysis of the results shows tha tthe factor of financial awards, work environment, labormarket considerations, personality and gender did not significantly influence the election of the public accounting profession andcorporate accounting profession. Anddiscriminant scores for the twogroups of the same accounting profession significantly, which means that thereisa different view for students who choose the public accounting profession and students who choose accounting profession companyKeywords:   Financial award, Work environment, Labor market considerations, Personality, Gender and the Accounting profession